Dry Sorbent Injection (DSI) System for the Abatement of VOCs from Gas Streams - Kalender, M.; Akosman, C. (Springer International Publishing Ag, 2015)
In this study, the removal of VOCs from gas streams was experimentally investigated by using dry sorbent injection (DSI) technique. The experimental studies were performed in a laboratory scale DSI set up. Chloroform and carbon tetrachloride were chosen as VOCs. The adsorbent for VOCs was commercial activated carbon (Envirocarb AP4-50). The DSI experiments were conducted using various initial bulk gas concentrations, different solid adsorbent loading rates, different gas flow rates, at temperature of 40 degrees C and the atmospheric pressure. The adsorption of VOCs on the activated carbon sample increased with increasing the particle residence time, the adsorbent loading, and the initial bulk gas concentration. But, the adsorption of VOCs decreased with the increase of the gas flow rate. The change of the adsorption rate with the particle residence time within a given, the adsorbent mass loading rate showed that the adsorption process carried out as a diffusion-controlled. It was also observed that the adsorption of chloroform on the activated carbon used was higher than that of carbon tetrachloride in all experimental conditions carried out. The experimental results were compared with the data obtained from solution of a theoretical model developed for DSI in literature. The Freundlich parameters (k(F) and q) of VOCs studied was determined by using a fixed bed in order to use in solutions the DSI model equations. The parameters such as phi(T), sigma(p) and d(pore) calculated from particle and pore size distribution data were used in the model solutions. The experimental results, especially at high solid adsorbent loading rates, were found to be in agreement with the DSI model solutions.
Keywords: Dry sorbent injection technique; VOCs; Adsorption; Activated carbon; Mathematical modelling